Effects of social demographic factors on leadership style in Serbian banking industry - Berber, Nemanja; Strugar Jelača, Maja; Bjekić, Radmila; Marić, Slobodan (Anali Ekonomskog fakulteta u Subotici, 2022)
The main aim of this paper is to investigate the effects that gender, age, and educational level have on leadership styles, based on the Multifactor Leadership Questionnaire (MLQ) methodology. The sample used in the research comprises 140 managers from the banking sector in Serbia. The research was performed in 2019. The research methodology includes a literature review in the area of leadership and a statistical analysis of the data collected. The regression models were created to investigate the relations between leadership styles and demographic factors of age and educational level of managers. The results of the research pointed that there are positive statistically significant relations between the transformational and transactional leadership styles and level of education, while in the case of age, there are negative relations observed. The authors presented practical and theoretical implications and limitations of the study.